Intermodulation due to interaction of photovoltaic inverter and electric vehicle at supraharmonic range - Abid, Fahim; Busatto, Tatiano; Ronnberg, Sarah K.; Bollen, Math H. J. (2016 17th International Conference on Harmonics and Quality of Power (ICHQP), 2016)
Advent of power electronic switching is introducing more and more non-linear loads in the low voltage grid. Besides harmonic current generation in the frequency range below 2 kHz, these non-linear loads are also responsible for current emission in the range of 2 kHz to 150 kHz, commonly known as supraharmonic emission. Supraharmonic currents mainly flow between nearby appliances and heavily influence the overall emission of neighboring devices. This paper presents an analysis of supraharmonic interaction between a photovoltaic inverter and an electric vehicle. It has been noticed that intermodulation distortion arises as a result of interaction between different switching frequencies used by the devices. Later, additional household equipment were added to photovoltaic and electric vehicle to observe their effect on intermodulation distortion. All the measurements were conducted in a controlled laboratory environment imitating a domestic customer.